An experimental analysis of the defect sensitivity of solid foams. (August 2018) - Chen, Shaohui; Isaksson, Per
Highlights: The fracture behavior of cellular materials with short cracks deviate from the prediction of traditional fracture theory. Cellular solids are tolerant to cracks shorter than a critical transition length. The critical transition crack length is related to the microstructure of the cellular material. Abstract: Single edge notched bending (SENB) and single edge notched tensile (SENT) fracture experiments were conducted to study the influence of the defect size on the global fracture behavior of three different brittle low-density PVC solid foams. It was found that for sufficiently small defects (initial cracks), the continued fracture process was through breakage of cell edges located at random positions far away from the defect while the global fracture load was fairly constant and hence unaffected by the initial defects. At defects larger than about four cells, however, the continued cell edge fractures were localized to the near vicinity of the defect, resulting in a decreasing global fracture load in accordance with classical linear elastic fracture mechanics theory. Hence a size of about four cells is considered to be a critical microstructure transition length, meaning that the foam is unaffected for defects smaller than this transition length from a fracture point of view.